Movimientos sociales en Madrid: ¿hay base crítica entre los universitarios para otro 15M? - Berumen, Sergio A.; Berumen, Regina (El Colegio de México, 2023)
15M was an assembly movement in 2011 that emerged within the framework of a severe crisis in Spain. Following the tenth anniversary of the events, this study explored the degree of knowledge among university students in Madrid about the main progressive ideas, the mark left by 15M and the degree of predisposition and sensitivity towards social movements. To this end, a survey was distributed through social media, which was answered by 642 subjects. The results revealed five profiles of clearly differentiated individuals.